Autopoiesis in Virtual Organizations - Pańkowska, Małgorzata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Virtual organizations continuously gain popularity because of the benefits created by them. Generally, they are defined as temporal adhocracies, project oriented, knowledge-based network organizations. The goal of this paper is to present the hypothesis that knowledge system developed by virtual organization is an autopoietic system. The term "autopoiesis" was introduced by Maturana for self-productive systems. In this paper, Wikipedia is described as an example of an autopoietic system. The first part of the paper covers a discussion on virtual organizations. Next, autopoiesis' interpretations are delivered and the value of autopoiesis for governance of virtual organizations is presented. The last parts of the work comprise short presentation of Wikipedia, its principles and conclusions of Wikipedia as an autopoietic system.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 102-110